The use and usefulness of artificial intelligence in international business education. Evidence from a field study - Holtbrügge, Dirk; Wicht, Luisa; Bernhard, Theresa (International Journal of Management Education, 2025)
This field study is among the first empirical investigations into the integration of an artificial intelligence (AI) enhanced video course in management and international business (IB) education. Moving beyond conceptual discussions, it evaluates the use and perceived usefulness of an AI-enhanced video course in a real classroom setting. Findings highlight that such AI tools support personalized learning, increase student engagement, and offer particular benefits for culturally diverse learners by reducing communication barriers and accommodating different educational backgrounds. While exploratory in scope, the study offers practical insights for educators seeking to implement AI in an inclusive and effective manner. Limitations include reliance on self-reported perceptions and a focus solely on student experiences. Future research should examine the impact of AI on learning outcomes and explore the reasons for using AI tools further, for example by investigating emotional and affective components.
CRIS-Team Scopus Importer:2025-09-12
Keywords: Artificial intelligence; Educational videos; Field study; International business education; Personalized learning; Usage; User satisfaction